Effects of ecological restoration on soil properties of the aeolian sandy land around Lhasa, southern Tibetan Plateau - Chengrui Liao (Ecosphere, 2020)
Abstract The ecological restoration of aeolian sandy land has not only improved the function of ecosystem services, such as wind prevention and sand fixation, but has also indirectly reduced the regional economic losses caused by sandstorms. However, the interaction between vegetation and soil properties after natural and artificial restoration of the sandy land in southern Tibetan Plateau has not been sufficiently studied. In the present study, we selected four vegetation types, including artificial forest (A), revegetated shrub (B), natural shrub (C), and natural grassland (D), in the sandy land in the middle reaches of the Yarlung Zangbo River basin, Tibet, China, and investigated the changes in soil particle size and nutrients at depths of 0–20 cm and 20–40 cm, finally examining the potential relationships between soil properties and leaf nutrients. Our results indicated that in the topsoil (0–20 cm), the natural shrub (C) and natural grassland (D) have greater silt content, recorded as 50.77% and 62.16%, respectively, compared to the artificial forest (A) and revegetated shrub (B). Natural grassland (D) had the highest silt content and the lowest soil bulk density (SBD) among the four vegetation types. There was no significant difference in the soil organic matter (SOM) in the topsoil of the different vegetation types. However, at the depth of 20–40 cm, the SOM content of the different vegetation types was in the following order: natural grassland (D) (23.37 g/kg) > natural shrub (C) (17.42 g/kg) > revegetated shrub (B) (14.85 g/kg) > artificial forest (A) (8.43 g/kg). The ammonium nitrogen content (NH4‐N) in the revegetated shrub (B) was higher compared to the other vegetation types. The SOM content was significantly correlated with the total phosphorus (TP) and available phosphorus (AP) of the sandy land. The leaf total carbon, nitrogen, and phosphorus exhibited a positive correlation with SBD, AP, and available potassium. These findings can provide useful information to optimize the patterns of natural and artificial restoration for controlling desertification in similar eco‐regions.